Meta-analysis on effect of essential oils and extracts of spices on the microbiological quality of meat and poultry products - Anggita, Gita; Budi, Faleh Setia; Kusumaningrum, Harsi Dewantari (Universiti Kebangsaan Malaysia, 2023)
Different spices have been reported containing antimicrobial compounds that can prevent or reduce the microbiological spoilage or pathogenic bacteria in meat or poultry products with various results. This study evaluated the effect of essential oils and extracts of spices in reducing bacteria in meat/poultry products using a meta-analysis approach by comparing the Hedges’d effect size (standardized mean difference, SMD, and 95% confidence interval, CI). A total of 240 data, extracted from 10 articles that were selected by Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) from 121 full-text articles, were analyzed using Meta Essential tools. The results showed that essential oils had a better cumulative significant effect in reducing bacterial loads of meat/poultry products (SMD=-4.37, 95%CI=-5.63 to -3.10) in comparison to the extracts (SMD=-3.66, 95%Cl=-4.56 to -2.76). As essential oils, cassia (SMD=-58.17, 95%CI=-109.88 to -6.47) showed the best effect size, whereas as extract, ganghwayassuk (SMD=-4.19, 95%CI=-6.22 to -2.16) was the most significant. Furthermore, the total plate count was significantly affected by cassia (SMD=-58.17, 95%CI=-109.88 to -6.47), Enterobacteriaceae by sage (SMD=- 5.93, 95%CI=-8.32 to -3.54), and coliform also by sage (SMD=-3.79, 95%CI=-6.76 to -0.82). In general, Salmonella spp. was found as pathogenic bacterium that was the most affected (SMD=-19.68 and 95%CI=-39.01 to -0.35). In the form of essential oils, dipping was the best way in reducing microorganisms, while as extracts, adding them in the products was the best method. This study provided reliable data in selecting spices for applications to improve the quality and safety of meat and poultry products.